A ideia-imagem: forma e representação na fotografia moderna - Salles, Filipe Mattos de (2011)
The present research has as its objective to discuss the question of the representation, truthfulness and fluidity of the images of the digital era, especially photographic images, which are considered by authors such as Barthes, Sontag, Santaella, Flusser, Benjamin, Aumont, and Couchot, among many others, as reliable representations of reality, means that allow different interpretations, but all of them unanimous in considering them as representations of what is real. On this research, I try to investigate what we call "reality and representation", and thus raise a question that presents itself indelibly today as an attack to the testimony of truthfulness: photographs today are very easily manipulated. At first, this was done through chemical processes, which implied handcrafted, specialized work, but nowadays it is available to everyone through widely spread software. Thus, more than ever it is necessary to reevaluate the notion that photography is a trustworthy source of existence, even considering a historical testimony. To what extent can one rely on that source? Where would the recognizable, trustworthy reality be? Such questions take us not to the photographic support in itself, but to its previous instance: the very idea of photography, or photography as an idea. In this study, the different ways of using photographic support were also analyzed, so as to shed light on the role of photojournalistic, advertising, social, historical, documental, and even tourism images. Before being considered as a communication phenomenon, the intense proliferation of images seen in the 20th century (and that has entered the 21st century with monumental strength) can be considered as a psychical phenomenon, given the near-pathological relationship that modern society has built with digital photography. In addition to the cited authors, Kossoy, Machado, Vasquez, Adams, Neiva Jr., Arnheim, Fernandes Jr., Francastel, Panofsky, Bresson, Joly, Plato, Jung, and Bazin, were also important reference sources in the development of the present research